Metode pembinaan Akhlakul Karimah melalui kegiatan keagamaan di SMA Negeri Gondangrejo - Nanda Qori Aina; Nurul Latifatul Inayati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This research aimed to describe and identify religious activity, method, supporting and inhibiting factors in the implementation of ahlakhul karimah development at SMAN Gondangrejo in academic year of 2022/2023. This study was a qualitative research that using phenomenological approach. The data sources of this research were school principal, teachers, and students. The data analysis technique of this research were data reduction, data presentation, and drawing or verifying conclusions. The data validity of this research used two types of triangulation, namely source triangulation and technical triangulation. The result of this research indicated that the methods used in developing akhlakul karimah in SMAN Gondangrejo were the habituation method, the exemplary method and the advice method. The religious activities that support the development of akhlakul karimah in SMAN Gondangrejo were religious Fridays, dzuhur and asar prayers simultaneously, dhikr together, discoursing after prayers, infaq after dzuhur and asar prayers togerther, SMAGO Muharram festival (SMF), and mabit. The supporting factors for the successful development of akhlakul karimah in SMAN Gondangrejo were derived from adequate school facilities, cooperation between teachers and students intersting. The inhibiting factors for the development of akhlakul karimah in SMAN Gondangrejo were android and the different environtments for students.